2017
DOI: 10.1038/s41598-017-02494-6
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2 promotes vasculogenic mimicry and tumor aggressiveness by upregulating Twist1 in gastric carcinoma

Abstract: High mobility group protein A2 (HMGA2) is a transcription factor that plays an important role in the invasion and metastasis of gastric carcinoma (GC). The term vasculogenic mimicry (VM) refers to the unique ability of aggressive tumour cells to mimic the pattern of embryonic vasculogenic networks. However, the relationship between HMGA2 and VM formation remains unclear. In the present study, we examined concomitant HMGA2 expression and VM in 228 human GC samples and 4 GC cell lines. Our data indicate that HMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 43 publications
(52 reference statements)
3
32
0
Order By: Relevance
“…The present results confirmed TNC upregulation in glioma tissues, especially in GBM tissues and show that 34% of samples were VM-positive, as reported previously 32 . We assessed VM formation in glioma cell lines and low-passaged primary cultured glioma cells, and found that TNC expression levels correlated with VM formation ability.…”
Section: Discussionsupporting
confidence: 93%
“…The present results confirmed TNC upregulation in glioma tissues, especially in GBM tissues and show that 34% of samples were VM-positive, as reported previously 32 . We assessed VM formation in glioma cell lines and low-passaged primary cultured glioma cells, and found that TNC expression levels correlated with VM formation ability.…”
Section: Discussionsupporting
confidence: 93%
“…miRNA-320a has been shown to be crucial for intestinal barrier integrity through modulation of the regulatory subunit PPP2R5B of phosphatase PP2A (38). In addition, miRNA-320a was found to both target ␤-catenin directly (39) and VE-cadherin through inhibition of the transcriptional repressor TWIST1 (40,41). miRNA-34a-5p has been shown to serve as an inhibitor for the zinc finger transcription factor Snail (42,43), which in turn functions as a transcriptional repressor of the adherens and tight junction proteins E-cadherin, claudin, and occludin (44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%
“…a and b ). Previously, reported results showed that the VM incidence in gastric carcinomas, cutaneous melanoma, esophageal stromal cancer, colorectal cancer and osteosarcoma were 28.5%, 34%, 33.3%, 19.2% and 22.7%, respectively . Intriguingly, the presence of VM is less than 50% in almost all cancer types examined to date; researchers suspect that VM may only exist in aggressive malignant sub‐phenotypes of cancers .…”
Section: Discussionmentioning
confidence: 99%